Keterwakilan Politik Perempuan dalam Pemilu Legislatif Provinsi Riau Periode 2014-2019 - Dessy Artina (Fakultas Hukum Universitas Islam Indonesia, 2016)
Women and men have equal position in politics; women’s participation is highly needed. Such thing is due to the fact that there are many issues regarding women’s interests requiring women’s representation in legislative institutions as well as regarding the 30% quota for women in the election of legislative members in Riau Province in 2014-2019. This research focuses on the level of women’s political representation in the legislative general election in Riau Province 2014 - 2019. This was a normative legal research. The data source was from primary and secondary law materials, and result of library research from various references. The finding shows that the level of women’s representation increases as expected from the policy regarding women’s representation.